ANALISIS KONTRIBUSI PERCEIVED EASE OF USE DAN TRUST TERHADAP KEPUASAN PENGGUNA VIRTUAL ACCOUNT DALAM KONTEKS PEMBAYARAN PENDIDIKAN - Fahira Fathana; Vivi Yosefri Yanti (Jurnal Interprof, 2025)
This study aims to examine how ease of use and trust affect student satisfaction when using virtual accounts to pay tuition fees. The research was conducted with a quantitative approach using the survey method. The population in this study were students of Universitas Muhammadiyah Muara Bungo who used virtual accounts for tuition payments. The sample in this study amounted to 53 people who met the criteria. The sampling technique used was purposive sampling, with the criteria that the respondent had made tuition payments using a virtual account. Data was collected through distributing online questionnaires using Google Form, then analyzed with the help of the SmartPLS application. Analysis of data was carried out to determine the effect of each factor separately or together on the level of student satisfaction. The results of this study show that ease of use and trust in virtual accounts affect student satisfaction in making tuition payments.